Pengaruh Biaya Standar Terhadap Pengendalian Biaya Produksi Studi Kasus Pada PT ITP, Tbk - Edison, Edison; Sapta, Untung (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
All companies have activities which are different each other in operation, but they have the same target, that is how the company can operate and grow continuously to meet the companyâs goal. Cost has an important role to the activities of the company. Production cost embraces: basic commodities expense, direct labours expense, and factory overhead expense. Thereby, itâs needed an adequate control towards productions cost in order to increase efficiency. An effective way to do control of production cost can be made based on standard cost. Standard cost constitutes cost determined previously to produce certain product unit before processing. In relation to cost control, standard cost concept forms data as analysis matter to find out the difference between actual cost and standard cost. In the implementation, it can be used variant analysis method to know margin degree during processing. Based on that comparison, it will be yielded variant or margin of production cost, either productive margin or negative margin. Then, non-profitable margin will be analyzed by the management to improve or revise the standard cost. Key words: the influence of standard cost; production cost control.